Natuna Fisheries Resources: DPSIR Framework - Gusti Gilang Ramadhan (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Natuna Waters have a high potential for fishery resources, including fish, shrimp, and other marine products. However, the potential faces serious problems, such as overfishing, illegal fishing, and conflict between local fishermen and high-tech foreign fishermen. In this paper, we apply the DPSIR (Driving forces, Pressures, State, Impact, and Response) framework to analyze the potential and problems of Natuna fisheries resources. We identified the driving and pressure factors affecting the condition of the waters, as well as the resulting impacts. We also discuss the responses that have been and are being made to address the issue. The results of the analysis showed that Natuna waters are under great pressure from human activities, especially overfishing and illegal fishing, which harm the sustainability of fishing resources in Natuna. This paper contributes to the understanding of the potential and problems of marine resources of Natuna waters, as well as informing policymakers about the policies that need to be taken to maintain the sustainability of marine resources (especially fisheries) in the region.